Manufacturing space homogeneity in additive manufacturing - electron beam melting case - Piaget, Alexandre (Strojniški vestnik, 2017)
This paper focuses on the manufacturing space homogeneity of the electron beam melting (EBM) technology. An Arcam AB A1 machine is used as tool for experimentations, with titanium (Ti-6Al-4V) as material. The objective of this study is to show the correlation between workpieces geometrical deformations and their position in the manufacturing space. Results show that the position on Z-axis does not affect quality, but there is a strong link in the Z-plane: significant defects appear near the manufacturing space boundaries. First manufactured layers are deformed in the vicinities of the manufacturing space edges. Up to 3 mm of material loss and 8mm of dimensional deformation are measured. Further analyses point that this phenomenon is particularly related to a sintering variation in the powder: there are up to 3 % density difference from the center to borders. To avoid the problem, reduction of the manufacturing space and a supporting strategy are proposed. Defects can also be removed by implementing thermal insulation on the machine or by modifying the beam operation.
Keywords: aditivne tehnologije; homogenost delovnega območja; upravljanje kakovosti